RECTIFIER ANTENNA UNTUK ENERGY HARVESTING GELOMBANG ELEKTROMAGNETIK - Sukriyah Buwarda (Journal of Science and Engineering, 2022)
The results of the study have obtained rectifier antennas that can convert electromagnetic waves into DC electrical energy. One of the energy harvesting methods is to use rectenna. Rectenna is an antenna that can capture electromagnetic waves that propagate freely in the air which is integrated with a rectifier that is able to convert electromagnetic waves into electrical energy. In this study, a series of power storage has been made with the aim of storing electrical energy generated by the rectifier. Two types of antennas with different frequencies are used as test equipment, namely a WiFi antenna that works at a frequency of 2.4 GHz and a TV antenna that works at a frequency of 470-806 MHz. From the results of the tests carried out, a voltage of 5.96 V was generated in the power storage circuit with a charging process duration of 54 minutes 27 seconds using a Wi-Fi antenna integrated with a rectifier and step up dc to dc converter. Meanwhile, by using a TV antenna, a voltage of 4.25 V is produced with a charging process duration of 57 minutes 19 seconds.